MISSIE - A new method to analyse performance parameters of figure skating jumps - Schaefer, K.; Brown, N.; Alt, W. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Competitive figure skaters have to perform triple and quadruple jumps with a high grade of execution. Monitoring flight time and rotational velocity, as the most critical parameters in successful figure skating jumps, objectifies and enhances feedback quality and quantity in the technique training process. 11 figure skaters performed 412 jumps on ice. All jumps were sampled with an inertial measurement system (MISSIE) and filmed with high speed video. With respect to time values of figure skating jump events toe pick, release of glide leg, take off and landing inertial data were manually and software algorithm analysed, and video data were manually analysed. Bland-Altman-Plots document very good performance of MlSSlE concerning raw data and analysis by software algorithm. MlSSlE can be used for figure skating jump analysis and feedback, being superior to traditional video analysis.